2020
DOI: 10.1029/2020gl087465
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Observations Identify Phytoplankton Community Composition as Driver of Carbon Flux Attenuation

Abstract: The attenuation coefficient b is one of the most common ways to describe how strong the carbon flux is attenuated throughout the water column. Therefore, b is an essential input variable in many carbon flux and climate models. Marsay et al. (2015, https://doi.org/10.1073/pnas.1415311112) proposed that the median surface water temperature (0–500 m) may be a predictor of b, but our observations from Arctic waters challenge this hypothesis. We found a highly variable attenuation coefficient (b = 0.43–1.84) in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
5
13
0
Order By: Relevance
“…On the other hand, several studies revealed limited export of Phaeocystis spp.-dominated blooms (Riebesell et al, 1995;Reigstad and Wassmann, 2007;Wolf et al, 2016), while others have reported significant contribution of this prymnesiophyte to export (Lalande et al, 2011;Moigne et al, 2015;Wollenburg et al, 2018), mainly as a consequence of deep mixing, aggregation, ballasting, or heavy grazing by large zooplankton who mediate export through the production of fast-sinking fecal pellets (Hamm et al, 2001;Reigstad and Wassmann, 2007;Boyd et al, 2019). This is consistent with a recent study, partly based on vertical export data presented herein, showing that the carbon flux attenuation coefficient is negatively correlated with the dominance of diatoms compared to non-ballasted Phaeocystis, and therefore, the relative contribution of diatoms is a good predictor for carbon flux attenuation in the upper 200 m of the water column, especially in the cold waters of the Arctic (Wiedmann et al, 2020).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, several studies revealed limited export of Phaeocystis spp.-dominated blooms (Riebesell et al, 1995;Reigstad and Wassmann, 2007;Wolf et al, 2016), while others have reported significant contribution of this prymnesiophyte to export (Lalande et al, 2011;Moigne et al, 2015;Wollenburg et al, 2018), mainly as a consequence of deep mixing, aggregation, ballasting, or heavy grazing by large zooplankton who mediate export through the production of fast-sinking fecal pellets (Hamm et al, 2001;Reigstad and Wassmann, 2007;Boyd et al, 2019). This is consistent with a recent study, partly based on vertical export data presented herein, showing that the carbon flux attenuation coefficient is negatively correlated with the dominance of diatoms compared to non-ballasted Phaeocystis, and therefore, the relative contribution of diatoms is a good predictor for carbon flux attenuation in the upper 200 m of the water column, especially in the cold waters of the Arctic (Wiedmann et al, 2020).…”
Section: Introductionsupporting
confidence: 92%
“…Phaeocystis, on the other hand, may form large blooms, but their contribution to carbon export is generally considered to be low (Reigstad and Wassmann, 2007;Wolf et al, 2016), unless ballasted by cryogenic gypsum (Wollenburg et al, 2018) or deep-mixed by eddies (e.g., Lalande et al, 2011). Recent findings also conclude that ballasted and sticky diatoms are generally poorly attenuated in the upper water column compared to non-ballasted Phaeocystis, and therefore, the relative contribution of diatoms is a good predictor for carbon flux attenuation, especially in the cold waters of the Arctic (Wiedmann et al, 2020). The current study found that the largest blooms were formed by Phaeocystis, but with loss rates <2% day −1 of POC standing stock and with average POC flux of 190 mg C m −2 day −1 at 100 m. The diatom bloom on the shelf break revealed very high POC export fluxes out of the epipelagic (Figure 8), with loss rates >2.5% day −1 and flux >450 mg C m −2 day −1 , despite having some nitrates and silicic acid available in the upper water column and a strongly stratified layer below the Chl a maximum.…”
Section: Seasonal Changes In Phytoplankton Community and Export Composition Are Reflected In The Magnitude Of Exportmentioning
confidence: 99%
“…With more than 1,000 described morphospecies (Poulin et al, 2011), Arctic diatoms exhibit a remarkable taxonomic diversity, along with a high degree of morphological, physiological and functional diversity (Fragoso et al, 2018). Accordingly, the abundance, community composition and distribution of diatoms in the Arctic realm ultimately shape ecosystem functioning (Wiedmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…ne key vector of the biological carbon pump is marine snow, representing large (>500 µm) particles of detritus (including zooplankton fecal pellets), organic matter (remnants and exudates of plankton), inorganic matter, and/or aggregated mixtures of those [1][2][3][4][5] . Changes in both phytoplankton and zooplankton community structure directly influence the quantity and composition of marine snow 6,7 and thus the efficiency of the biological carbon pump 8,9 . Many previous biogeochemical models 5,10,11 and calculations estimating carbon export, based on in situ observations [12][13][14] , assumed a fixed mass to volume relationship and simple geometry of particles, such as spheres or a defined fractal dimension.…”
mentioning
confidence: 99%